Shrimp Antiviral mja-miR-35 Targets CHI3L1 in Human M2 Macrophages and Suppresses Breast Cancer Metastasis - Chen, Yulei; Zhang, Siyuan; Cao, Jiao; Zhang, Xiaobo (Frontiers in Immunology, 2018)
Virus infection can change host’s metabolism, while tumorigenesis results from metabolic disorder. MicroRNAs (miRNAs), crucial regulatory factors overlaying transcriptional control mechanisms, can guide metabolic homeostasis. In terms of metabolic disorder, antiviral miRNAs may have anti-tumor activity. However, this issue has not been extensively investigated. In the present study, the results revealed that shrimp mja-miR-35, which showed antiviral activity in shrimp against white spot syndrome virus (WSSV) infection, could suppress the metastasis of breast cancer by targeting human CHI3L1 gene of M2 macrophages in a cross-phylum manner. Furthermore, the feed expressing shrimp mja-miR-35 had antiviral capacity in shrimp and anti-tumor activity in humans, leading to the simultaneous control of virus infection and tumor progression. Therefore, our findings indicated that the antiviral miRNAs derived from shrimp stress responses against virus infection might be an important source of human anti-tumor drugs and miRNAs could bridge the control of aquaculture diseases and the prevention of human tumors.